The effect of problem based learning (PBL) model accompanied multirepresentation based LKPD on learning outcomes - Tiastutik, Fuji; Mahardika, I Ketut; Ahmad, Nur (International Journal for Educational and Vocational Studies, 2023)
This study is useful to know the influence of learning models problem based learning (PBL) accompanied multirepresentation based LKPD of science learning outcomes of Junior High School Class VIII. This is quasi-experimental study. Population wear class VIII students SMP Negeri 10 Jember. The research sample was determined using the method purposive sampling area namely class VIII G as many as 33students and class VIII H as many as 32 students. Learning tools in the form of (1) syllabus, (2) lesson plan, and (3) LKPD based on multirepresentation. The main data retrieval technique is test in the form of a description of 10 questions that lead to higher older thinking skill (HOTS) to see the result of congnitive learning carried out tests pretest, posttest, and the grid of the questions. Supporting data retrieval techniques are monitoring sheets, interviews, and documentation. The result of the research were normality test and homogeneity test approved so that the average score posttest different experimental and control class learning outcomes or learning models problem based learning (PBL) accompanied multirepresentation based LKPD affect the learning outcomes of Junior Hight School science class VIII. The statement proves that learning using PBL learning model with multirepresentation based LKPD allows achieving learning science learning outcomes.